The Helsinki Effect : International Norms, Human Rights, and the Demise of Communism - Thomas, Daniel C. (Daniel Charles) (Book collections on Project MUSE., 2001)
In The Helsinki Effect, author Daniel Thomas argues that the Helsinki Final Act 1975 transformed East-West relations and provided a common platform around which opposition could mobilise.